Association between Tooth and Type of Instrument Fractured During Root Canal Treatment - Krisha Doshi1 , S.Delphine Priscilla Antony2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Instrument fracture is a common unfortunate event that takes place during the root canal treatment. A goodknowledge about the different instruments that can fracture, causes of fracture, predilection of teeth towardsfracture of instruments, etc will help the clinician to be more alert. It will also help clinicians gain confidencetowards methods of retrieval of these instruments. The aim of this study was to analyse the associationbetween the tooth and the type of instrument separated during root canal treatment. The study was basedon an online setting. Data was collected retrospectively. Patient reports of 86000 patients that reported tothe institution between June 2019 and March 2020 were reviewed. Data of instrument retrievals done fromDecember 2019 to March 2020 was collected. Excel sheet tabulations were made involving tooth number,type of instrument fractured and method of retrieval. Descriptive statistics was done on SPSS software.Association between the tooth and type of instrument was analyzed with Chi Square test. No statisticalsignificant difference was seen between the tooth and type of instrument fractured. (p>0.05). The tooth typedoes not influence the type of instrument fractured significantly